2020
DOI: 10.1152/ajpheart.00542.2019
|View full text |Cite
|
Sign up to set email alerts
|

Reduced stiffness and augmented traction force in type 2 diabetic coronary microvascular smooth muscle

Abstract: We show here that a potential causative factor for reduced diabetic coronary microvascular stiffness is the direct reduction in coronary vascular smooth muscle cell stiffness. These cells were also able to generate enhanced traction force, validating previously published computational models. Collectively, these data show that smooth muscle cell stiffness can be a contributor to overall tissue stiffness in the coronary microcirculation, and this may be a novel area of interest for therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…This should allow for maintenance of the intracellular (cytoskeletal) and extracellular matrix structures that affect the mechanical properties of the vascular wall. Indeed, it has been shown that cytoskeletal structures, such as Factin stress fibers, as well as extracellular matrix components, such as elastin and collagen, participate in providing mechanical strength to the vascular wall under passive conditions, albeit each at different intravascular pressures (113)(114)(115)(116)(117)(118)(119)(120). In addition, to avoid a major involvement of the axial component in the strain and stress assessment, vessels should be extended to eliminate any bending or bowing at the maximal intraluminal pressure used.…”
Section: Mechanical Analysismentioning
confidence: 99%
“…This should allow for maintenance of the intracellular (cytoskeletal) and extracellular matrix structures that affect the mechanical properties of the vascular wall. Indeed, it has been shown that cytoskeletal structures, such as Factin stress fibers, as well as extracellular matrix components, such as elastin and collagen, participate in providing mechanical strength to the vascular wall under passive conditions, albeit each at different intravascular pressures (113)(114)(115)(116)(117)(118)(119)(120). In addition, to avoid a major involvement of the axial component in the strain and stress assessment, vessels should be extended to eliminate any bending or bowing at the maximal intraluminal pressure used.…”
Section: Mechanical Analysismentioning
confidence: 99%
“…Regional micromechanics of grafts were measured using atomic force microscopy (AFM). 28 30 Tissue sections were de-paraffinized with xylene washes and rehydrated through graded alcohols, followed by overnight immersion in PBS at room temperature. Micromechanical properties of tissue samples were characterized using the Asylum MFP-3D-Infinity-BIO AFM.…”
Section: Methodsmentioning
confidence: 99%
“…The Young’s modulus of each point was determined by fitting force-indentation data from 40 curves to the Oliver-Pharr model (a modified Hertz model) using IGOR Pro software (WaveMetrics). 28 , 33 …”
Section: Methodsmentioning
confidence: 99%
“…Atomic force microscopy (AFM) provides nanoscale resolution of the biomechanical properties of soft biological tissues, including the vasculature [ 17 , 19 ]. AFM-based studies have successfully uncovered changes in arterial stiffness in response to hypertension [ 14 , 20 ], diabetes [ 21 , 22 ], and aging [ 14 , 23 ], but to our knowledge, it has not been used to map sex-related differences in media-layer stiffness under physiological conditions. Another useful technique to interrogate arterial stiffness is via functional studies incorporating uniaxial circumferential loading in a wire myograph.…”
Section: Introductionmentioning
confidence: 99%
“…Another useful technique to interrogate arterial stiffness is via functional studies incorporating uniaxial circumferential loading in a wire myograph. Large artery compliance is tightly regulated by VSM reactive properties, including contraction and relaxation [ 24 ], and there seems to be a linear relationship between stiffness and traction force development [ 25 ], which has been confirmed in diabetic coronary microvascular SMCs [ 21 ]. However, how AFM-based medial-layer stiffness results associate with force development in isolated aortas is unknown.…”
Section: Introductionmentioning
confidence: 99%